The role of trait emotional intelligence in diabetes self-management behaviors: The mediating effect of diabetes-related distress. (1st September 2018) - Schinckus, Louise; Avalosse, Hervé; Van den Broucke, Stephan; Mikolajczak, Moïra
Abstract: This article presents two studies about trait emotional intelligence (EI) and diabetes. The first study investigated whether the level of trait EI of people with diabetes differs from the non-diabetes population. The second study explored the impact of trait EI on diabetes-related distress and diabetes self-management behaviors. Methods: In study 1, an existing database of 8532 members of a health insurance fund was analyzed through group comparisons to investigate whether the level of trait EI of people suffering from diabetes differs from the non-diabetes people sharing the same gender, age, education level and BMI. Study 2 consisted of a survey among 146 persons with diabetes to investigate the relations between trait EI, distress and diabetes self-management behaviors through regressions and mediation analyses. Results: People suffering from diabetes had significantly lower levels of trait EI than controls, but this difference was essentially due to differences in gender, age, educational level and BMI. However, trait EI influenced diabetes self-management behaviors. This relationship was mediated by diabetes-related distress, which proved to be a better predictor of self-management behaviors than depression or anxiety. Conclusion: These findings suggest that enhancing trait EI can be an appropriate way to reduce the distress associated with diabetes management and the risk of complications. Highlights: People with diabetes have a significantly lower level of trait EI than controls. This difference disappears when pairing participants (age, gender, education, BMI). Trait EI predicts diabetes self-management. Distress is a mediator between trait EI and diabetes self-management.